Trypanosoma cruzi-like bloodstream trypomastigotes in bats from the State of Piauí, Northeastern Brazil - Artur da S. Pinto; Dalva N. da Costa Bento (Sociedade Brasileira de Medicina Tropical (SBMT), 1986)
One-hundred and thirty-five bats from 12 species were examined for thepresence of trypomastigotes by means of direct blood examination, xenodiagnosis, and hemoculture. Of those, 44 specimens (32.6%) from 8 species were infected with trypanosomes. Phyllostomus discolor discolor presented the highest rate of infection, being captured only in one locality, while Phyllostomus hastatus hastatus captured in four localities showed high rates. Two species, Anoura geoffroyii and Pteronotus (Phillodia) pamelli rubiginosa, were found infected by T. cruzi-like trypanosomes, apparently described for thefirst time. Flagellates from Artibeus jamaisensis jamaisensisa and A. geoffroyii were able toproduce detectable parasitaemia in young mice. One triatomine bug was found infected in natural conditions, Triatoma brasiliensis was associated with a P.h. hastatus colony, in which six captured bats were also found infected. Cento e trinta e cinco morcegos, pertencentes a 12 espécies diferentes, foram examinados quanto à presença de tripomastigotas sangüíneos, por meio do exame direto do sangue, xenodiagnóstico e hemocultura. Deles, 44 exemplares (32.6%), pertencentes a 8 espécies, estavam infectados por flagelados semelhantes ao T. cruzi. P. d. discolor apresentou a mais elevada taxa de infecção, sendo capturado em apenas uma localidade, enquanto que P. h. hastatus, capturado em quatro localidades, apresentou também altas taxas de infecção. Duas espécies, A. geoffroyii e P. (P.) pamellii rubiginosa foram encontradas infectadas por flagelados semelhantes ao T. cruzi, aparentemente pela primeira vez. Flagelados provenientes das espécies A. j. jamaisensis e A. geofforyii foram capazes de produzir parasitemia em camundongos jovens. Um exemplar de T. brasiliensis, infectado em condições naturais, foi encontrado associado a uma colônia de P. h. hastatus, na qual seis morcegos também foram encontrados infectados.